ANALISIS DAN RANCANGAN SISTEM INFORMASI SIRKULASI BUKU BERBASIS INTERNET OF THINGS DALAM MENINGKATKAN KUALITAS LAYANAN PERPUSTAKAAN UNIVERSITAS SURABAYA - Nancy Elisabeth; Adhicipta Raharja Wirawan (Perpustakaan Universitas Surabaya, 2018)
Accounting information system becomes an important role for a business entity both profit business entity and non profit business entity. In fact, in the operational activities of the University Surabaya’s Library on Tenggilis, the existing information systems are still not working optimally and causing various problems. The findings of researchers are relate to differences in the status of books, length ofbook search on the shelf, as well as the number of queues that are sometimes long at certain hours also vandalism. For that, we need an analysis and system design that can help solve existing problems. This study aims to determine how the system design, especially on service cycle based on IoT in improving the quality of service at the Ubaya’s Library on Tenggilis. This recommendation used System Development Life Cycle from system analysis stage to physical design stage which is limited to relationship database creation. Researchers recommend NFC-tags, smart shelf library systems, smart libraries, AppIT, hand-held readers, SMS Gateway also reward and punishment system.